Elafin and its precursor trappin‐2: What is their therapeutic potential for intestinal diseases?. (28th November 2022) - Deraison, Céline; Bonnart, Chrystelle; Langella, Philippe; Roget, Karine; Vergnolle, Nathalie
Abstract : Elafin and its precursor trappin‐2 are known for their contribution to the physiological mucosal shield against luminal microbes. Such a contribution seems to be particularly relevant in the gut, where the exposure of host tissues to heavy loads of microbes is constant and contributes to mucosa‐associated pathologies. The expression of trappin‐2/elafin has been shown to be differentially regulated in diseases associated with gut inflammation. Accumulating evidence has demonstrated the protective effects of trappin‐2/elafin in gut intestinal disorders associated with acute or chronic inflammation, or with gluten sensitization disorders. The protective effects of trappin‐2/elafin in the gut are discussed in terms of their pleiotropic modes of action: acting as protease inhibitors, transglutaminase substrates, antimicrobial peptides or as a regulator of pro‐inflammatory transcription factors. Further, the question of the therapeutic potential of trappin‐2/elafin delivery at the intestinal mucosa surface is raised. Whether trappin‐2/elafin mucosal delivery should be considered to ensure intestinal tissue repair is also discussed.